Possibilities for re-envisioning the work of the teacher in early childhood education. Notes for a polyphonic and participatory university practice. Issue 2 (15th March 2023) - Ceballos, Noelia; Saiz-Linares, Ángela; Susinos-Rada, Teresa
ABSTRACT: We analyse a training proposal in the Degree in Early Childhood Education at the University of Cantabria (Spain), which consists of the elaboration of a critical and collaboratively created dictionary of concepts identified as important by the participating students. Through enquiry projects in which they adopt the role of researchers, they construct new definitions that affirm the plurality of languages and diversity of experiences and knowledge that form part of the school reality. These three enquiry projects allow us to discuss the diverse professional models of early childhood education (the maternalistic assumption, the outcome pedagogy and the critical ecology of the profession). In addition, we describe and analyse the enquiry processes employed with a special focus on listening processes for the different voices (non-directivity or respect for ideas in their interpretation and representation) and the difficulties encountered. Finally, the proposal makes it possible to explore the political and structural implications of teacher training (the theory–practice relationship and the need for an integrated training model).